Financial cycles, credit bubbles and stabilization policies - Luisa Corrado; Tobias Schuler (European Central Bank (ECB), 2019)
This paper analyzes the effects of several policy instruments for mitigating financial bubbles generated in the banking sector. We augment a New Keynesian macroeconomic framework by endogenizing boundedly-rational expectations on asset values of loan portfolios, allow for interbank trading and show how a credit bubble can develop from a financial innovation. We then evaluate the efficacy of several policy instruments in counteracting financial bubbles. We find that an endogenous capital requirement reduces the impact of a financial bubble significantly while central bank intervention ("leaning against the wind") proves to be less effective. A welfare analysis ranks the policy reaction through an endogenous capital requirement highest. We therefore provide a rationale for the use of countercyclical capital buffers.
Keywords: E44; E52; 330; Basel III; credit-to-GDP gap; CCyB